What do laboratory-forgetting paradigms tell us about use-inspired forgetting? - Scotti, Paul S. (Cogn Res Princ Implic, 2021)
Directed forgetting is a laboratory task in which subjects are told to remember some information and forget other information. In directed forgetting tasks, participants are able to exert intentional control over which information they retain in memory and which information they forget. Forgetting in this task appears to be mediated by intentional control of memory states in which executive control mechanisms suppress unwanted information. Recognition-induced forgetting is another laboratory task in which subjects forget information. Recognizing a target memory induces the forgetting of related items stored in memory. Rather than occurring due to volitional control, recognition-induced forgetting is an incidental by-product of activating items in memory. Here we asked whether intentional directed forgetting or unintentional recognition-induced forgetting is a more robust forgetting effect. While there was a correlation between forgetting effects when the same subjects did both tasks, the magnitude of recognition-induced forgetting was larger than the magnitude of directed forgetting. These results point to practical differences in forgetting outcomes between two commonly used laboratory-forgetting paradigms.